2019
DOI: 10.1371/journal.pone.0225739
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of conditioned medium released by tonsil-derived mesenchymal stem cells in a chronic murine colitis model

Abstract: Tonsil-derived mesenchymal stem cells (TMSC) have characteristics of MSC and have many advantages. In our previous studies, intraperitoneal (IP) injection of TMSC in acute and chronic colitis mouse models improved the disease activity index, colon length, and the expression levels of proinflammatory cytokines. However, TMSC were not observed to migrate to the inflammation site in the intestine. The aim of this study was to verify the therapeutic effect of conditioned medium (CM) released by TMSC (TMSC-CM) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…However, to date, the effect of T-MSCs-CM has not been investigated thoroughly compared to that of T-MSCs themselves. A prior study for chronic colitis model showed that T-MSCs-CM-treated group has an equivalent effect to T-MSCs-treated group regarding the immunomodulatory effect [27]. Consistent with this, the addition of T-MSCs-CM on the AR mouse model showed a similar immunomodulatory effect, compared with the previous study regarding T-MSCs on the AR mouse model.…”
Section: Discussionsupporting
confidence: 72%
“…However, to date, the effect of T-MSCs-CM has not been investigated thoroughly compared to that of T-MSCs themselves. A prior study for chronic colitis model showed that T-MSCs-CM-treated group has an equivalent effect to T-MSCs-treated group regarding the immunomodulatory effect [27]. Consistent with this, the addition of T-MSCs-CM on the AR mouse model showed a similar immunomodulatory effect, compared with the previous study regarding T-MSCs on the AR mouse model.…”
Section: Discussionsupporting
confidence: 72%
“…can affect the final outcome of the treatment of UC [37]. MSCs could be easily isolated and are amplified from several tissues for the treatment of UC, including bone marrow-derived stem cells (BMSCs) [38], adipose tissue-derived stem cells (adSCs) [29], umbilical cord stem cells (UCSCs) [39], endometrial regenerative cells (EndSCs) [40], placenta [41], intestinal stem cells (ISCs) [42], amnion [43], amniotic fluid [44], and tonsil [45]. Their routes of administration were reported to be intraperitoneal (IP), intravenous (IV), subcutaneous (SC), endoscopic, systemic, or anal injection, which can affect the outcome of cell transplantation in UC [46][47][48].…”
Section: The Therapeutic Role Of Mscs In Ucmentioning
confidence: 99%
“…Tonsil-derived stem cells (TSCs) and CM derived from TSCs illustrated equivalent effects in the improvement of inflammation in a DSS-induced colitis mice model. After cell therapy, weight gain, recovery of colon length, reduction of disease activity index, and decrease in the expression level of the proinflammatory cytokines, interleukin (IL)-1β, IL-6, and IL-17, were visible [45] (Table 7). Table 7.…”
Section: In Vivo Studies On Treatment Of Uc Using Other Sources Of Mscsmentioning
confidence: 99%
“…The higher convenience of obtaining adipose and umbilical cord MSCs has also increased their application across several studies [3,62]. Other sources of MSCs applied in IBD and colitis-associated CRC are amniotic fluid [63], placenta [64], tonsil [65], amnion [66,67], and endometrium regenerative cells [68], among others. The routes of administration are intraperitoneal, intravenous, and anal injection.…”
Section: Interaction Between Msc Ibd and Ibd-associated Crcmentioning
confidence: 99%